2020
DOI: 10.3389/fnut.2020.563605
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Effects of Gut Metabolites: Exploring the Path of Dietary Prevention of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) has increased over the past half century and has now become the second most frequent autoimmune disease in childhood and one of major public health concern worldwide. Evidence suggests that modern lifestyles and rapid environmental changes are driving factors that underlie this increase. The integration of these two factors brings about changes in food intake. This, in turn, alters epigenetic regulations of the genome and intestinal microbiota composition, which may ultimately play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 175 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…DNA analyses allowed for the identification of 88 methylation sites in B cells including those influencing genes related to the pathogenesis of diabetes such as HLA and subunit β of the interleukin receptor 2 (IL-2Rβ), and in terms of the entire genome of human pancreatic islets, 383 potential methylation locations have been identified [179]. Studies indicate that micro-RNA can participate in the autoimmune damage to β cells, regulation of the synthesis and release of insulin, and consequently, the pathogenesis of type 1 diabetes [181].…”
Section: Perspectives and Conclusion-can Nutrigenomics Be The Future?mentioning
confidence: 99%
“…DNA analyses allowed for the identification of 88 methylation sites in B cells including those influencing genes related to the pathogenesis of diabetes such as HLA and subunit β of the interleukin receptor 2 (IL-2Rβ), and in terms of the entire genome of human pancreatic islets, 383 potential methylation locations have been identified [179]. Studies indicate that micro-RNA can participate in the autoimmune damage to β cells, regulation of the synthesis and release of insulin, and consequently, the pathogenesis of type 1 diabetes [181].…”
Section: Perspectives and Conclusion-can Nutrigenomics Be The Future?mentioning
confidence: 99%
“…Recent research has addressed the role of the gut microbiome in autoimmune diseases [ 80 , 81 , 82 ]. Longitudinal studies on humans revealed that the diversity and intestinal dysbiosis of microbiota, which is regarded as a group of beneficial microorganisms, were decreased in patients with T1D.…”
Section: Overview Of the Modulatory Effects Of Host Microbiota On Autoimmune Diseasesmentioning
confidence: 99%
“…Nutrition is the main modulator of bacterial composition and abundance in the gastrointestinal tract, suggesting the opportunities for therapeutic nutritional approaches to manipulate microbiota composition and diversity [14,15]. Nutrigenomics and nutritional microbiomics approaches have received increasing attention and are currently being used to study respectively the mutual interactions between food and genes and between diet and microbiota in several diseases including cancer [16,17], cardiovascular [18,19], metabolic [20], and autoimmune diseases [21][22][23][24] in order to enable their better understanding, prevention and treatment through optimization of individuals' dietary intakes.…”
Section: Introductionmentioning
confidence: 99%